A review on regulations, current status, effects and reduction strategies of emissions for marine diesel engines. (1st November 2020) - Ni, Peiyong; Wang, Xiangli; Li, Hu
Highlights: Regulations on marine diesel engine emissions are listed and compared. The contribution of marine diesel engine emissions to regional emissions is given. The emission levels of marine diesel engines are reviewed. Integrated multi-pollutant aftertreatment technologies are reviewed. Abstract: Marine diesel engines, which provide main power source for ships, mainly contribute to air pollution in ports and coastal areas. Thus there is an increasing demand on tightening the emission standards for marine diesel engines, which necessitates the research on various emission reduction strategies. This review covers emission regulations and emission factors (EFs), environmental effects and available emission reduction solutions for marine diesel engines. Not only the establishment of the emission control areas (ECAs) in the regulations but also many experiments show high concerns about the sulfur limits in fuels, sulfur oxides (SOx) and nitrogen oxides (NOx) emissions. Research results reveal that NOx emissions from marine diesel engines account for 50% of total NOx in harbors and coastal regions. Sulfur content in fuel oil is an important parameter index that determines the development direction of emission control technologies. Despites some issues, biodiesel, methanol and liquefied nature gas (LNG) play their important roles in reducing emissions as well as in replacing fossil energy, being promising fuels for marine diesel engines. Fuel-water emulsion (FWE) and exhaust gas recirculation (EGR) are effective treatment option for NOx emissions control. Common rail fuel injection is an effective fuel injection strategy to achieve simultaneous reductions in particulate matter (PM) and NOx. Selective catalytic reduction (SCR) and wet scrubbing are the most mature and effective exhaust aftertreatment methods for marine diesel engines, which show 90% De-NOx efficiency and 95% De-SOx efficiency. It can be concluded that the integrated multi-pollutant treatment for ship emissions holds great promise.